Storing JWT Token in Local Variables - Bulgakova, O.S.; Zosimov, V.V.; Popravkin, P.D. (Control systems & computers, 2020)
The article discusses the problem of storing structured information over the Internet (JSON format) in local storage and pieces of information transmitted to the browser from the site visited by the user (cookies), and a method is proposed for storing the JSON web key in a local variable inside the closure (functions that refer to into independent variables). Based on user authorization, the interaction of the JSON web key with the server is shown, and the solution to the main problems of authorization and storage of the token JWT (JSON Web Token).